Synthesis, spectral and thermal studies on dicarboxylate-bridged palladium(II) coordination polymers. Part I - Fernandes, R. L. [UNESP]; Takahashi, P. M. [UNESP]; Frem, R. C. G. [UNESP]; Netto, A. V. G. [UNESP]; Mauro, A. E.; Matos, J. R. (Springer, 2009)
This work describes the synthesis, IR and (13)C CPMAS NMR spectroscopic as well the thermal characterization of the new dicarboxylate complexes [Pd(2)(ox)(2)(4,4'-bipy)]n (1), [Pd(2)(ox)(2)(bpe)](n) (2) and [Pd(2)(ox)(2)(pz)](n) (3) {ox = oxalate, bipy = 4,4'-bipyridine, bpe = 1,2-bis(4-pyridyl)ethane, pz = pyrazine}. TG experiments reveal that compounds 1-3 undergo thermal decomposition in three steps. Metal palladium was the final product of the thermal decompositions, which was identified by X-ray powder diffraction.
Keywords: (13)C CPMAS NMR; IR; Oxalate; Palladium(II); Thermal behavior